TANNIN LEVELS IN LEAVES OF SOME OAK SPECIES AT DIFFERENT STAGES OF MATURITY - Makkar, H P S; DAWRA, R K; Singh, B (JOURNAL OF THE SCIENCE OF FOOD AND AGRICULTURE, 1991)
Total phenolics, condensed tannins, degree of polymerisation, protein precipitation capacity, protein precipitable phenolics and specific activity (protein bound per unit tannins) were determined in the leaves of four oak species at different stages of maturation (4 days old to 1 year old). The content of total extractable phenols was higher in younger leaves in Quercus ilex Linn, Quercus semecarpifolia Sm and Quercus serrata Roxb, whereas in Quercus glauca Thunb the content was higher in the mature leaves. In all species studied, condensed tannins increased with maturation. Protein precipitation capacity had a trend similar to that of total phenols. In Q serrate and Q semecarpifolia the apparent degree of polymerisation increased, and the content of protein precipitable phenolics and specific activity decreased as the leaves matured. The decrease in protein precipitation capacity with maturation in these two species may be explained by both the decrease in the content and the change in the nature of phenols capable of binding proteins. Protein precipitation capacity was not detectable in Q ilex leaves. Protein precipitation capacity in the mature leaves decreased in the order of Q serrata > Q semecarpifolia > Q glauca > Q ilex.
Keywords: CONDENSED TANNINS; Tannins; TOTAL PHENOLS